Evaluating Zoysiagrass-Tall Fescue Mixtures in Kansas - Mingying Xiang; J. Fry; M. Kennelly (Kansas Agricultural Experiment Station Research Reports, 2016)
Seeding zoysiagrass at 1 lb PLS/1,000 sq ft in June with subsequent seeding of tall fescue into established zoysiagrass in September at 8 lbs PLS/1,000 sq ft resulted in the best mixture of these two species.
Keywords: Turfgrass; zoysia; tall fescue